Hak dan Kewajiban Anggota Keluarga dalam Perspektif Kekerasan dan Tindak Pidana dalam Keluarga - Maghrabi, Ahmad Maulana; Anwar, Syahrul (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
The relationship among family members ideally should be based on love, mutual respect, and the fulfillment of rights and obligations. However, in reality, an imbalance in the execution of rights and obligations often triggers conflicts that can lead to domestic violence (DV). This violence not only impacts the victims physically and psychologically, but it can also have legal consequences in the form of criminal acts. Therefore, understanding the rights and obligations of family members is important to reduce the potential for violence within the family. The research method used in this study is a literature review related to the rights and obligations of family members. The rights and obligations of family members are the fundamental basis for building resilience and harmony in households. Every member has complementary roles which create balance in family relationships. With the synergy between family awareness, community support, and state law enforcement, violations of rights and obligations can decrease and diminish. Ultimately, the balance in the implementation of the rights and obligations of family members not only prevents criminal acts within the family but also strengthens the foundation of a just, prosperous, and civilized society.